The effect of telerehabilitation on quality of life, anxiety, and depression in children with cystic fibrosis and caregivers: A single-blind randomized trial - KENİŞ COŞKUN, ÖZGE; KARADAĞ SAYGI, NAİME EVRİM (My University, 2022)
Background Postural and aerobic exercises are essential in rehabilitation in cystic fibrosis (CF). The aim of this study is to examine the effect of telerehabilitation on the quality of life, depression, and anxiety levels of children with CF and their caregivers\" mood and anxiety levels. Materials and Methods Patients between the ages of 6-13 with CF were randomized into two groups. Study group received an exercise program three times a week via Zoom for 12 weeks. Cystic Fibrosis Revised Questionnaire (CFQ-R), Anxiety and Depression Scale in Children-Revised (RCADS) were applied to the patients and State-Trait Anxiety Scale (STAI) and Beck Depression Inventory (BDI) were applied to the caregivers in the beginning and at the end of the program. Patients\" FEV1 levels and 6-min walk tests were also measured. Results Twenty-eight patient-caregiver dyads, 14 dyads in each group, completed the study. The initial mean RCADS-Major depressive disorder score of the patients in the exercise group was 6.21 +/- 3.11, and this value decreased to 3.92 +/- 3.79 at the end of the study and was significantly better (p < 0.02). A similar significant change was observed when the RCADS-generalized anxiety disorder score decreased from the initial mean level of 6.28 +/- 2.81 to 3.42 +/- 2.65 (p < 0.01). There were significant changes in improvement in the body image in telerehabilitation group. Similar significant changes were not observed in the control group. Caregivers\" anxiety and depression levels did not change significantly. Conclusion A short-term telerehabilitation program improved patients\" anxiety and depression levels, body image, and functional status. However, caregiver anxiety and depression levels did not change significantly.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Göğüs Hastalıkları ve Allerji; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; Chest Diseases and Allergy; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); SOLUNUM SİSTEMİ; PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); RESPIRATORY SYSTEM; Pediatrics; Respiratory Care; Pediatrics, Perinatology and Child Health; Pulmonary and Respiratory Medicine; anxiety; cystic fibrosis; quality of life; rehabilitation; telehealth; PSYCHOMETRIC PROPERTIES; EXERCISE; SCALE; VERSION